An analysis of feasibility study of computer information system - Ho, Chee Meng; Nanda, Navnit Kumar; Nagarur, Nagendra N.; Zhao, Ming; JICA (Bangkok : Asian Institute of Technology, 1990)
A survey of feasibility study of computer information system is conducted in this study with the objectives of identifying the potential problems and pitfalls when conducting a feasibility study. An analysis of the result of the survey result is done to achieve that purpose and also to correlate the problems encountered in the study with factors like the size of information system done . Possible solutions are recommended based on the finding of the survey done. Differences in perceiving the importance of various factors when doing a feasibility study among data processing and non data processing oriented staff is also conducted, with the objective of understanding the differences in perception so as to avoid in future system studies failure due to these problems.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: System analysis; Information storage and retrieval systems